2020
DOI: 10.1007/s10843-019-00266-z
|View full text |Cite
|
Sign up to set email alerts
|

Service innovation and internationalization in SMEs: antecedents and profitability outcomes

Abstract: Both innovating and internationalizing can hold the key to survival and growth among small-and medium-sized enterprises (SMEs). Service innovation in particular is highly relevant in the increasingly digitalized and high-technology global trade. However, there have been until now few studies on service innovation in international entrepreneurship. Thus, in an effort to illuminate its role in entrepreneurial internationalization, the present study examines the profitability impact of service innovation in SME i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 170 publications
(247 reference statements)
1
28
0
2
Order By: Relevance
“…) Elements of HC among others help in identifying business opportunities and exploiting them (Mansion & Baush 2019;Ruzzier et al2007), thus forming the bases for international growth. Surprisingly, Vuorio et al (2020) did not find HC to have any effect on mostly small ICT firms' internationalization. This can be however be explained by the fact that they did not include international experience as part of the measurement of HC.…”
Section: Intellectual Capital and International Growth Of Firmsmentioning
confidence: 75%
“…) Elements of HC among others help in identifying business opportunities and exploiting them (Mansion & Baush 2019;Ruzzier et al2007), thus forming the bases for international growth. Surprisingly, Vuorio et al (2020) did not find HC to have any effect on mostly small ICT firms' internationalization. This can be however be explained by the fact that they did not include international experience as part of the measurement of HC.…”
Section: Intellectual Capital and International Growth Of Firmsmentioning
confidence: 75%
“…Studies confirm that innovation strategies and technology enable firms to expand and compete internationally ( Amankwah-Amoah et al, 2018 ; Bortoluzzi et al, 2018 ; Pino Soto, 2018 ; Donbesuur et al, 2020 ; Vuorio et al, 2020 ). For instance, researchers have argued that formulating new technological strategies and adopting present ones are critical for firms’ productivity and the knowledge economy ( Wamboye et al, 2015 ; Wong, 2015 ; Schniederjans, 2017 ).…”
Section: Introductionmentioning
confidence: 95%
“…The financial outcomes related to innovation include growth in sales, growth in profits and a higher return on assets. Vuorio et al (2020) concluded that firms with weaker innovation outcomes have lower profitability margins.…”
Section: Performance Outcomesmentioning
confidence: 99%